Measuring and Analyzing the Reality of a Pivotal Application (the Educational Institution’s Strategy and Governance and Management) According to the Iraqi Institutional Accreditation Standards: A Comparative Study - Apd, Dhuha Razak; Ali Abdel Karim Al-Saffar; Marwa Mustaph Al-Roubaie (Journal of Techniques, 2023)
The research aims to identify the possibility of measuring and analyzing the reality of the application of institutional accreditation standards in the two surveyed universities (Al-Karkh Science and Al-Farahidi Private University). The problem of the study is examining the applied reality of the axes of institutional accreditation in Iraqi public and private universities. Determining the gap between the actual performance of the two universities surveyed and a pivotal application (the strategy of the educational institution / governance and administration). The study aims to identify the applied reality of the axes of institutional accreditation in Iraqi public and private universities. Narrowing the gap, enhancing strengths and addressing weaknesses by measuring and diagnosing the gap between the actual reality of the performance of the two universities and the application of the pivotal Iraqi institutional accreditation. The checklists that were developed according to the paragraphs of the two axes (indicators), and the use of mathematical equations to analyze and collect the weights of these indicators, and to extract application percentages and gaps (24%, 24%) is lower than the Al-Farahidi Civil University, where the gap for the two axes (33%, 39%) was lower.